Book Review: Dance, Place, and Poetics: Site-Specific Performance as a Portal to Knowing - Bergonzoni, Carolina (Journal of the Canadian Association for Curriculum Studies, 2023)
Celeste Nazeli Snowber’s 2022 book Dance, Place, and Poetics: Site-Specific Performance as a Portal to Knowingcannot fully be captured in a review. The book combines dance videos, sound recordings, poetry and incredible photos. The author offers a refreshing and rejuvenating yet radical approach to a relational understanding of ourselves and others, both humans and non-humans. In this text, I walk the reader through the book. I summarize and highlight the main themes and trends as they relate to curriculum studies.